The self-management training program teaching developmentally disabled individuals to manage their disruptive behavior - Pflugrad, Diane; Karan, Orv C. (Wisconsin : University of Wisconsin Board of Regents [production company] ; Illinois : Research Press, 1984)
Disscussed the disruptive developmentally disabled individuals.
Accompanied by training manual
Copy available in DVD format
Editor, Tom Piatt ; script, Christine L. Cole
Narrator: Marshall Poole
Keywords: Developmentally disabled; Mentally handicapped -- Behavior modification; Handicapped